Continuous and Discrete Deformation Modes of Mechanical Metamaterials With Ring-Like Unit Cells - Yang, Nan; Zhuang, Juncheng; Wei, Shichuan; Yu, Ying (Frontiers in Physics, 2022)
Structures with multiple deformation paths provide a promising platform for robotics and reprogrammable mechanical and thermal deformation materials. Reconfigurations with a multi-path can fulfill many tasks (e.g., walking and grasping) and possess multiple properties (e.g., targeted Poisson’s ratio and thermal expansion coefficient). Here, we proposed a new ring-like kirigami structure and theoretically and experimentally found that for a basic unit, there are four discrete deformation patterns and a continuous shearing deformation pattern; thus, there are a large number of discrete deformation patterns for a multi-unit combination with geometrical compatibility coupled with a shearing deformation mode. Moreover, targeted Poisson’s ratios (either + or -) in the x- and y-directions can be realized by inversely designing the geometrical parameters for a certain deformation path. Additionally, we showed the capability of constructing 2D and 3D cellular structures in various patterns with the proposed ring-like units. The multiple deformation modes demonstrated here open up avenues to design new reprogrammable materials and robots across various scales.